ROTATIONALLY AND VIBRATIONALLY INELASTIC-SCATTERING OF 4(1) D2CO - Kroes, G; Echave, J; Clary, D (1992)
Results of quantum calculations on rotationally and vibrationally inelastic scattering of S1 (1Ã) D2CO by He and Ar are presented. The azimuthal and vibrationally close-coupled, infinite-order sudden method is used. The extremely anharmonic ν4 bending mode of S1 D2CO is modelled using a double minimum potential. Large cross sections are predicted for collision-induced relaxation of the ν4 mode. Also, a large steric effect is predicted for energy transfer to this mode: collisions with the D2-end of the molecule are far more effective in promoting vibrational energy transfer than collisions with the O-end. It should be possible to measure this steric effect in an experiment which employs a beam of oriented D2CO molecules. The cross sections for pure rotational excitation are fitted well to an exponential energy gap law for both collision partners. In contrast, the rotationally resolved cross sections for vibrational deactivation show considerable structure. The results presented here can serve as predictions for experiments that are currently being carried out. © 1992.